2010
DOI: 10.1007/s11095-010-0200-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Crystal Size on the In Vitro Dissolution and Oral Absorption of Nitrendipine in Rats

Abstract: The dissolution rate and the oral bioavailability of nitrendipine were significantly affected by the crystal size, and the oral bioavailability could be improved significantly by preparing it as nanocrystals. FaSSIF can be used to predict differences in oral absorption of crystals with different particle sizes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
47
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(51 citation statements)
references
References 40 publications
1
47
1
1
Order By: Relevance
“…A previous study found that oral absorption of a drug is influenced by particle size, which affects the dissolution rate. 26 However, the current study found no statistically significant difference in particle size or any other particle characteristics between HMw-NPC and LMw-NPC (Table 1). Thus, particle size and other characteristics might not be responsible for the different bioavailability and absorption results for HMw-NPC and LMw-NPC.…”
contrasting
confidence: 64%
“…A previous study found that oral absorption of a drug is influenced by particle size, which affects the dissolution rate. 26 However, the current study found no statistically significant difference in particle size or any other particle characteristics between HMw-NPC and LMw-NPC (Table 1). Thus, particle size and other characteristics might not be responsible for the different bioavailability and absorption results for HMw-NPC and LMw-NPC.…”
contrasting
confidence: 64%
“…Moreover, the nanometer-sized particles of carvedilol nanosuspensions could enable the interfacial interaction with the mucin layer, thereby further enhancing the absorption of carvedilol from the intestinal lumen. 21 Meanwhile, SDS used in the nanosuspensions and microsuspensions could improve the intestinal absorption of carvedilol from the intestinal epithelium by the paracellular pathway. 31 The presence of SDS and VES in the suspensions could also contribute to the increased saturation solubility of carvedilol, and thus improve the absorption of the drug.…”
Section: In Vitro Dissolution Studiesmentioning
confidence: 99%
“…21,22 However, the preparations used were stabilized by different types or ratios of stabilizers, which may not truly reflect the effects of particle size. Until now, research studies of particle size effect using carvedilol particles stabilized with the same kind and content of stabilizers have scarcely been reported.…”
Section: Introductionmentioning
confidence: 99%
“…This could be explained by the Noyes-Whitney equation. 33,34 As when drug particles are smaller, the corresponding surface area is larger, so the nanoparticles provided a large increase in the surface area. Furthermore, according to the Prandtl equation, 35 the diffusion distance, h, decreases for very small particles.…”
mentioning
confidence: 99%